1999
DOI: 10.1590/s0104-42301999000200007
|View full text |Cite
|
Sign up to set email alerts
|

Peritonite bacteriana espontânea na cirrose hepática: prevalência, fatores preditivos e prognóstico

Abstract: RESUMO -OBJETIVO. Investigar prevalência, fatores preditivos e prognóstico dos episódios de 11,12,16 . Taxas relativamente mais altas, chegando até 26%, têm sido registradas nos estudos prospectivos realizados na década de 80, onde paracentese abdominal passou a ser realizada de rotina 1,2,4,5,6,9,10,13 . As décadas de 80/90 assistiram a um aumento significativo do número de publicações sobre PBE. Entretanto, em nosso meio, poucos autores publicam dados a este respeito 4,8,[13][14][15][16] . Além disso, nosso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…The incidence of SBP in this sample was 11% and is similar to other Brazilian studies [7,21,22]. The low incidence of such infection could be explained by the fact that most of the ascitic fluid samples were collected in the outpatient setting and is in accordance with the incidence reported in the literature for this population [7,22].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of SBP in this sample was 11% and is similar to other Brazilian studies [7,21,22]. The low incidence of such infection could be explained by the fact that most of the ascitic fluid samples were collected in the outpatient setting and is in accordance with the incidence reported in the literature for this population [7,22].…”
Section: Discussionsupporting
confidence: 89%
“…23 These findings were similar to those of a Brazilian study, conducted in Rio de Janeiro, which showed that in 39.9% of the cases, the etiology related to alcohol, 28.7% viruses, 11.9% mixed causes (alcohol and virus) and 14.7% a variety of causes. 18 The prevalence of alcoholism in Brazil has been reported to range from 7.6% to 9.2%, which emphasizes the importance of this etiology as a cause of cirrhosis in our setting. 24 Even though SBP is diagnosed as an ascitic liquid neutrophil count ≥ 250 cells/mm 3 , cellularities of up to 8,000 neutrophils per mm³ have been described.…”
Section: Discussionmentioning
confidence: 88%
“…Ascitic fluid should be cultured at bedside in blood culture bottles, as soon as the paracentesis is done, as firstly demonstrated by Runyon and colleagues (1987) in order to achieve a positive result in almost 91% of the samples. Although many studies have confirmed Runyon’s results, Brazilian studies could not reach this accuracy in isolating SBP pathogens (Sette et al 1986; Mattos 1994; Figueiredo et al 1999; Coral et al 2002). In our studied group of patients, ascitic fluid culture was positive in only 28.5% of samples although it has been cultured at bedside and in accordance to previously described standard techniques.…”
Section: Diagnosismentioning
confidence: 97%
“…First of all, the results of culture are not readily available, which postpones the diagnosis and treatment of the infection. Secondly, one of the most frequent variants of ascitic fluid infection is culture-negative neutro-cytic ascites, which occurs in approximately 30% to 50% of patients (Sette et al 1986; Runyon et al 1987; Figueiredo et al 1999; Coral et al 2002). …”
Section: Diagnosismentioning
confidence: 99%